Product Pricing Based on Accounting Costs. - Lere, John C. (The Accounting Review, 1986)
Abstract ABSTRACT: Since various accounting costs are used in product pricing decisions, this paper' Identifies conditions under which a particular product cost is appropriate for use in product pricing. The approach used is to compare 'the output price selected Using three accounting costs commonly used in pricing with the output price selected by a utility-maximizing decision maker conducting a complete analysis. This comparison indicates conditions under which each accounting cost leads to prices closest to those obtained after a complete analysis and is used to develop testable hypotheses about costing method use.